Influencing Factors of Thermal Deformation on Hydrostatic Pressure Mechanical Seal and Optimization of Rotating and Stationary Rings - WeiBing Zhu; HeShun Wang; Lin Dong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
According to thermo-elastic deformation theory, take the temperature field analysis results of hydrostatic pressure mechanical seal as volume load to resolve the problem of thermal-structure coupling deformation of rotating and stationary rings in ANSYS software. The distribution laws of thermal strain, thermal stress and thermal-structure coupling deformation are obtained. The effects of working, material and structural parameters on axial, radial thermal deformation and deformation taper of the end faces are discussed in detail, and the main affecting factors are found out. Measures and structural constraint programs to control the thermal deformation are put forward. Base on the theory of thermal deformation compensation, the rotating and stationary rings are optimized, and the thermal deformation before and after their optimization are solved respectively and analyzed comparatively to verify the feasibility of the optimization program. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2049